Assessing the Impact of Marketing Mix and Halal Awareness on Consumer Purchase Behavior: A Case in Indonesia - Aini, Syafina Fauziyah; Hendrsato, Nur; Haidar, Abdullah (SMART Insight, 2024)
This research aims to analyze the influence of the marketing mix (product, price, place and promotion) and halal awareness on purchasing decisions for Mie Gacoan products in Karawang. This research is important because it combines two key factors, namely marketing strategy and halal awareness, which have not been widely studied simultaneously in the context of spicy food in Indonesia. Using descriptive quantitative methods, data from 400 respondents was analyzed using multiple linear regression. The research results show that product, place and promotion have a significant influence on purchasing decisions, while price and halal awareness do not have a significant influence. This research makes an original contribution to the sharia marketing literature by demonstrating the importance of product innovation and marketing strategies in improving purchasing decisions, while halal awareness needs to be further explored to increase its impact on Muslim consumers.